The effect of Co doping on the magnetic and magnetocaloric properties of Pr0.7Ca0.3Mn1−xCoxO3 manganites. Issue 6 (July 2015) - Selmi, A.; M'nassri, R.; Cheikhrouhou-Koubaa, W.; Boudjada, N. Chniba; Cheikhrouhou, A.
Abstract: In this work, we report the effect of low amount of cobalt doping at the Mn-site on the magnetic and magnetocaloric properties of Pr0.7 Ca0.3 Mn1− x Co x O3 (0≤ x ≤0.1) powder samples. Our samples, elaborated using the solid–solid reaction method at high temperature, are single phase and crystallize in the orthorhombic system with Pnma space group. While the parent compound Pr0.7 Ca0.3 MnO3 exhibits a charge order state at low temperature, the substituted samples with low amount of cobalt exhibit a paramagnetic to ferromagnetic transition with decreasing temperature. The Curie temperature T C increases with Co content from 105 K for x =0 to 116 K for x =0.1. The maximum values of the magnetic entropy change | Δ S M max | are found to be 0.8 J/kg K, 2.2 J/kg K, 3.1 J/kg K and 3.2 J/kg K in a magnetic field change of 5 T for x =0, 0.02, 0.05 and 0.1 respectively. The maximum value of the relative cooling power RCP is found to be 378.2 J/kg in the Pr0.7 Ca0.3 Mn0.95 Co0.05 O3 at 5 T. This value of RCP is about 92% of that obtained in gadolinium metal, known as one of the most important materials for magnetic refrigeration, at the same magnetic field change of 5 T.